2019
DOI: 10.1534/g3.119.400021
|View full text |Cite
|
Sign up to set email alerts
|

When West Meets East: The Origins and Spread of Weedy Rice Between Continental and Island Southeast Asia

Abstract: Weedy crop relatives are among the world’s most problematic agricultural weeds, and their ability to rapidly evolve can be enhanced by gene flow from both domesticated crop varieties and wild crop progenitor species. In this study, we examined the role of modern commercial crop cultivars, traditional landraces, and wild relatives in the recent emergence and proliferation of weedy rice in East Malaysia on the island of Borneo. This region of Malaysia is separated from the Asian continent by the South China Sea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The common wild rice (O. rufipogon) has been found to contribute to the evolution of sympatric weedy rice in South and Southeast Asia, however, studies do not show direct evolution of WR from O. rufipogon, indicating crop-wild hybridization (reviewed by Burgos et al, 2021). In Malaysia and Thailand, studies on WR using SSRs and SNPs revealed natural gene flow and hybridization between known wild rice and cultivated rice as the major causes of occurrence and spread of WR biotypes (Pusadee et al, 2013;Song et al, 2014;Neik et al, 2019;Vigueira et al, 2019;Wedger et al, 2019). Characterization of WR phenotypes in South Asia, and their associated candidate genes, contributes to the emerging understanding of mechanisms by which WR evolves worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The common wild rice (O. rufipogon) has been found to contribute to the evolution of sympatric weedy rice in South and Southeast Asia, however, studies do not show direct evolution of WR from O. rufipogon, indicating crop-wild hybridization (reviewed by Burgos et al, 2021). In Malaysia and Thailand, studies on WR using SSRs and SNPs revealed natural gene flow and hybridization between known wild rice and cultivated rice as the major causes of occurrence and spread of WR biotypes (Pusadee et al, 2013;Song et al, 2014;Neik et al, 2019;Vigueira et al, 2019;Wedger et al, 2019). Characterization of WR phenotypes in South Asia, and their associated candidate genes, contributes to the emerging understanding of mechanisms by which WR evolves worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Weedy rice has also evolved through hybridization between different cultivated rice varieties (Ishikawa et al, 2005; Qiu et al, 2014). In regions with wild Oryza species, weedy rice has evolved directly from wild rice ( O. rufipogon ) or through crop‐wild hybridization (Huang et al, 2017; Neik et al, 2019; Song et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Oryza rufipogon is interfertile with both domesticated and weedy rice, and while some traits of the wild species would be expected to be maladaptive for weedy rice in the agricultural fields where it specializes ( e.g ., perenniality and prostrate growth), other wild rice traits are likely advantageous ( e.g ., seed shattering, seed dispersal structures such as awns, and seed dormancy). In keeping with this expectation, candidate gene and neutral marker studies of weedy rice populations in Southeast and South Asia have indicated that wild rice can contribute to local weed evolution by hybridization and adaptive introgression 33 39 . However, whereas temperate weedy rice has been extensively examined through whole genome sequence analysis 28 , 30 32 , genome resequencing of tropical Asian weedy rice has so far been limited 28 .…”
Section: Introductionmentioning
confidence: 90%